Cappelli green di ieri e di oggi: intrecci e rifrazioni in fogge e materiali. Il caso niniche - Daniela Cacia (ZoneModa Journal)
The various influences that inspired fashion between the late nineteenth and early twentieth centuries profoundly transformed hat design and also contributed to the renewal of the Italian lexicon by introducing new terms. This paper explores the topic through the descriptions and images featured in fashion magazines and mail-order catalogs from the early decades of the twentieth century. Particular attention is given to the case of the Niniche hat, whose name exemplifies the phenomenon of deonymic derivation, offering insight into the interplay between fashion and language.